Does a switch of budget regimes constrain managerial discretion? Evidence for Italian public enterprises investment - Elisabetta Bertero; Laura Rondi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This study examines the effect of the hardening of the budget constraint on the investment behaviour of Italian state owned enterprises (SOEs). It carries out a natural experiment that exploits the 1987 shift of budget regimes due to the pressure of European Union economic policies on the Italian government. Drawing from the theory of capital market imperfections, we apply the empirical framework for the analysis of investment-cash flow sensitivity to a panel of state-owned manufacturing firms during the period 1977-93. We parallel state firms to Anglo-Saxon public corporations which, under separation of ownership and control, are afflicted by agency problems, managerial discretion, misallocation of free cash-flow and overinvestment. We argue that, under a soft budget constraint, state firms' managerial discretion and, in particular, collusion between managers and vote-seeking politicians, lead to wasteful investment.
Keywords: G32; L32; M40; G31; E32; 330; capital markets imperfections; public enterprises; investment and cash flow; soft-budget constraint; managerial discretion; Italian firms; Öffentliches Unternehmen; Betriebliche Investitionspolitik; Budgetrestriktion; Italien